2015
DOI: 10.1038/ncomms8353
|View full text |Cite|
|
Sign up to set email alerts
|

Epstein–Barr virus-encoded microRNA BART1 induces tumour metastasis by regulating PTEN-dependent pathways in nasopharyngeal carcinoma

Abstract: Epstein–Barr virus (EBV), aetiologically linked to nasopharyngeal carcinoma (NPC), is the first human virus found to encode many miRNAs. However, how these viral miRNAs precisely regulate the tumour metastasis in NPC remains obscure. Here we report that EBV-miR-BART1 is highly expressed in NPC and closely associated with pathological and advanced clinical stages of NPC. Alteration of EBV-miR-BART1 expression results in an increase in migration and invasion of NPC cells in vitro and causes tumour metastasis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 65 publications
(82 reference statements)
3
169
0
Order By: Relevance
“…EBV miR-BART1-5p and BART1-3p are dramatically increased in the N2-3 stages or advanced stages (III-IV) of NPC (Cai et al, 2015;Zheng et al, 2016). The levels of both miR-BART7 and miR-BART13 in NPC plasma are found to be present at distinct levels among patients with different stages of NPC, with elevated levels among patients with advanced disease.…”
Section: Ebv-encoded and Ebv-dysregulated Mirnas Are Potential Biomarmentioning
confidence: 84%
“…EBV miR-BART1-5p and BART1-3p are dramatically increased in the N2-3 stages or advanced stages (III-IV) of NPC (Cai et al, 2015;Zheng et al, 2016). The levels of both miR-BART7 and miR-BART13 in NPC plasma are found to be present at distinct levels among patients with different stages of NPC, with elevated levels among patients with advanced disease.…”
Section: Ebv-encoded and Ebv-dysregulated Mirnas Are Potential Biomarmentioning
confidence: 84%
“…Interestingly, recent investigations of potential EBV microRNA target genes revealed an inhibition of PTEN and extensive deregulation of several pathways involved in NPC. We previously reported that alteration of EBV-miR-BART1 and EBV-miR-BART7 expression results in migration and invasion of NPC cells through directly targeting tumour suppressor PTEN [29, 30]. Therefore, it suggests a possibility that aberrant CpG island methylation of PTEN confers “the second or additional hit” in NPC cells that contain EBV encoded microRNAs targeting this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, among 24 upregulated miRNAs differently expressed between NPC and nonmalignant nasopharyngeal samples, Cai and coworkers found that EBV miR-BARTs were more than twice the number of endogenous human miRNAs (62.5% vs 29.2%, respectively) [76]. The upregulation of BART miRNAs was also reported in mice xenograft tumors produced from EBV-positive carcinoma cells C666-1 (nasopharyngeal) and AGS-BX1 (gastric), as well as the EBV-positive BL36 (Burkitt Lymphoma) [77].…”
Section: Ebv In Cancer Progression: Lmps and Ebnas Are Not The Wholementioning
confidence: 99%